1995
DOI: 10.1002/art.1780380807
|View full text |Cite
|
Sign up to set email alerts
|

Increased susceptibility to oxidation of low‐density lipoproteins isolated from patients with systemic sclerosis

Abstract: Objective. To examine the resistance to oxidation of low-density lipoproteins (LDL) from patients with systemic sclerosis (SSc) and primary Raynaud's phenomenon (RP) compared with healthy controls.Methods. Plasma LDL were isolated from patients with diffuse cutaneous and limited cutaneous SSc (dcSSc and IcSSc, respectively), patients with primary RP, and healthy control subjects. The lipoproteins were assessed for their resistance to oxidation in the presence of cupric ions, using spectrophotometric assays.Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
1
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(42 citation statements)
references
References 37 publications
0
39
1
1
Order By: Relevance
“…Thus, increased levels of malondialdehyde in the circulation, in settings of platelet activation, may arise as a consequence of platelet activation rather than lipid peroxidation. A recent study (27) found that low-density lipoproteins from patients with scleroderma were more susceptible to oxidation than were those from healthy controls. Those authors concluded that the findings supported the hypothesis that free radical damage is involved in the development of scleroderma, and they suggested that direct measurement of oxidative stress in scleroderma would be of interest.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, increased levels of malondialdehyde in the circulation, in settings of platelet activation, may arise as a consequence of platelet activation rather than lipid peroxidation. A recent study (27) found that low-density lipoproteins from patients with scleroderma were more susceptible to oxidation than were those from healthy controls. Those authors concluded that the findings supported the hypothesis that free radical damage is involved in the development of scleroderma, and they suggested that direct measurement of oxidative stress in scleroderma would be of interest.…”
Section: Discussionmentioning
confidence: 98%
“…These 2 elements can thus overlap, jeopardizing the integrity of the vessel wall. In genetically predisposed SSc patients, characterized by ischemia and oxidative stress, 68 with raised levels of LDL undergoing oxidation, triggering vessel wall inflammation, 69 the overlap with SSc-dependent endothelial injury creates a noxious loop involving the microcirculation and macrocirculation. In this scenario, pathogenetic factors participating in endothelial sufferance, such as anti-endothelial cell antibodies, dysfunction of the fibrinolytic and coagulation system, and an increase of circulating levels of homocysteine, soluble intercellular adhesion molecule-1, and CRP may contribute significantly to increased risk of developing accelerated macrovascular disease.…”
Section: Macrovascular Disease and Atherosclerosis In Systemic Sclerosismentioning
confidence: 99%
“…Reference Evidence in vivo Herrick et al [49] Reduced micronutrient antioxidants in SSc Levels of vitamin C, vitamin E, and other dietary antioxidants lower in SSc patients -suggests increased susceptibility to reactive oxygen species Bruckdorfer et al [50] Reduced in vitro LDL oxidation lag-time in SSc Oxidation lag time in vitro is reduced for LDL isolated from SSc patients' serum. Suggests greater susceptibility to oxidation in vivo.…”
Section: Potential Involvement Of Oxidant Stress In Systemic Sclerodementioning
confidence: 98%